A complex programmed logic device‐based experiment system for the principles of computer composition. Issue 4 (21st March 2022) - Wu, Zhen; Deng, Ming; Zhang, Qisheng
Abstract: "The Principles of Computer Composition" is an important and fundamental core course in computing education. Recently, significant advancements have been made for experimental instruments that are related to "The Principles of Computer Composition" for colleges in terms of their functions and performances. However, most instruments are old, prone to failure, and are rarely automated. Some experimental systems use field‐programmable gate array (FPGA) or a complex programming logic device (CPLD); however, the systems still use numerous integrated discrete and small‐scale chips, which limits the functionalities of FPGA or CPLD chips. It is difficult to reconfigure the logic in all aspects of the experiment, and only a limited part of the logic can be reconstructed. Meanwhile, simulation experiments alone are too abstract for students to intuitively understand the circuit structures of the hardware. To address these issues, a CPLD‐based experiment system for the course "The Principles of Computer Composition" was designed. The proposed system has a flexible design with clear circuit structures and a high degree of automation and stability. In addition, it comes with multiple functions, including logic reconstruction. The test results prove that the proposed system can help students obtain a better understanding of the course content. The system meets the design goal, and it contributes to the development of computing education.